Deficiency of the Insulin-Like Growth Factor-Binding Protein Acid-Labile Subunit (ALS) of the Circulating Ternary Complex in Children with Short Stature - Domene, Horacio Mario (2010)
The acid-labile subunit (ALS) protein is a key component of the circulating 150-kDa IGF ternary complex. The main role of ALS is the extension of IGF-I half life by protecting it from degradation and preventing the passage of IGF-I to the extravascular compartment. In humans, complete ALS deficiency is characterized by severe reduction of IGF-I and IGFBP-3 that remain low after GH treatment, associated with mild growth retardation, much less pronounced than the IGF-I deficit. Pubertal delay in boys and insulin insensitivity are common findings. At least 21 patients with ALS deficiency have been described presenting 16 different homozygous or compound heterozygous inactivating mutations of the IGFALS gene. Although the effect of ALS deficiency on prenatal growth is still uncertain, postnatal growth is clearly affected, with the majority of the patients presenting a height between -2 to -3 SDS before and during puberty. In the assessment of a child with short stature ALS deficiency should be considered in those patients presenting: 1) a normal response to GH stimulation test, 2) low IGF-I levels associated with more profoundly reduced IGFBP-3 levels, 3) a mild growth retardation, apparently out of proportion to the degree of IGF-I and IGFBP-3 deficits, 4) lack of response to an IGF generation test and 5) insulin insensitivity. The relatively mild growth retardation in relation to the severe IGF-I deficit might be related to the preserved autocrine/paracrine action of locally produced IGF-I. The observation that in families of ALS deficient patients, heterozygous carriers for IGFALS gene mutations, are shorter than their wild type relatives and the relatively high frequency of heterozygosity for this gene in children with idiopathic short stature suggests a requirement of normal levels of ALS for the attainment of maximal growth potential.